Living wall systems for improved thermal performance of existing buildings. (January 2022) - Fox, Matthew; Morewood, Jack; Murphy, Thomas; Lunt, Paul; Goodhew, Steve
Abstract: Living wall systems are a relatively new form of façade cladding treatment on buildings. Bringing a host of benefits such as added biodiversity, they also have the potential to aid the thermal efficiency of a wall construction by offering an extra layer of thermal resistance. Yet few studies have been conducted to ascertain the thermal influence of living wall systems can have on existing buildings. This study reviews the impact of living walls upon the thermal and environmental performance of buildings and isolates a lack of research that directly measures associated retrofitted living wall thermal performance. A case study then monitors the heat flux through a pre 1970s uninsulated cavity masonry wall construction that has been retrofitted with an external living wall system face. Results are compared with an identical wall build-up on the same elevation without the living wall cladding. Results found that the calculated thermal transmission value for the pre 1970s wall with an additional Living wall façade cladding was 31.4% lower than that of the same wall without the living wall. Furthermore, diurnal fluctuations in heat flux were lower over the study period for the wall with the living wall system cladding. These findings demonstrate that a living wall façade offers a viable solution for helping to minimise heat loss from existing buildings of this construction. Highlights: Green and living facades can improve the thermal performance of existing buildings. There is a lack of empirical data on effects of living wall to building insulation. Findings demonstrate a 31% improvement to traditional masonry wall U-values.